A different shade of blue. Peacekeeping by confrontation: The Canadian contingent in Cyprus, 1964-1975. - Gravelle, Robert J. A. R. (University of Ottawa (Canada), 1995)
The study of conflict management in the post war period has encompassed various aspects, including the debates over the usefulness of international attempts in the maintenance of peace and security. Since 1945, Canada has been involved in all major United Nations peacekeeping missions including observation operations from 1945-1956, peacekeeping operations from 1956 to the present, and peace enforcement operations since 1991. The Canadian literature on peacekeeping missions has centred on foreign and defence policy questions and their influence on international affairs from a Canadian perspective. To fully appreciate the nature of peacekeeping operations in their foreign and defence policy contexts, we need to understand better how individual operations function, the principal problems encountered, and the way such operations have ended over time. This study of the United Nations Force in Cyprus (UNFICYP) is an analysis of a Canadian military operation and the evolution of peacekeeping from 1964-1975, with emphasis on the crucial 1974 period, which witnessed the Canadian Contingent's leading role in redefining the concept and practice of peacekeeping in Cyprus. Overnight it went from peacekeeper in an inter-communal situation to a peacemaker in a full scale war. The development of confrontational tactics in pressing cease-fires and in stabilizing the main confrontational area of Nicosia by declaring UN protected areas and the willingness to use force to retain these areas, was a major innovation in its modus operendi. The rendering of humanitarian assistance to both communities during the war and the protection of more than 200,000 refugees also necessitated the UN force to adopt new methods of providing aid. The UN presence was instrumental in saving countless lives and preventing a number of atrocities. The involvement of the UN through its presence in the cease-fire negotiations and the delineation of cease-fire lines underlined the important role and influence of the force that led to the ending of hostilities between the Turkish army and the Greek Cypriot National Guard. The leading role and influence which the Canadian Contingent exerted in UNFICYP, resulting in changing the concept and practice of peacekeeping in Cyprus, has been to this point overlooked.
Keywords: History, Modern.